Antioxidant Properties of “Natchez” and “Triple Crown” Blackberries Using Korean Traditional Winemaking Techniques - Youri Joh; Niels Maness; William McGlynn (International Journal of Food Science)
This research evaluated blackberries grown in Oklahoma and wines produced using a modified traditional Korean technique employing relatively oxygen-permeable earthenware fermentation vessels. The fermentation variables were temperature (21.6°C versus 26.6°C) and yeast inoculation versus wild fermentation. Wild fermented wines had higher total phenolic concentration than yeast fermented wines. Overall, wines had a relatively high concentration of anthocyanin (85–320 mg L−1 malvidin-3-monoglucoside) and antioxidant capacity (9776–37845 µmol Trolox equivalent g−1). “Natchez” berries had a higher anthocyanin concentration than “Triple Crown” berries. Higher fermentation temperature at the start of the winemaking process followed by the use of lower fermentation/storage temperature for aging wine samples maximized phenolic compound extraction/retention. The Korean winemaking technique used in this study produced blackberry wines that were excellent sources of polyphenolic compounds as well as being high in antioxidant capacity as measured by the Oxygen Radical Absorbance Capacity (ORAC) test.